(untitled) (Journal of Forensic Medicine & Toxicology, 2022)
Background: Transplantation of human tissues or organs is done to increase the life expectancy of an individual. However, organ donors are scarce to organ recipients, due to various factors. Legal in India, the procedure of transplantation is slow due to lack of awareness and knowledge in the community. Objective: To evaluate the level of Awareness, Knowledge and Perception on Organ Donation among the students of Health care Profession. Materials & methods: The study was conducted with total of 300 medical students participated in the Department of Forensic Medicine and Toxicology, Mahatma Gandhi Medical College and Research Institute, Puducherry with a self – designed questionnaire mailed as Google Form. The study tool used in this study is Likert Scale. The data analyzed and the results were automated accordingly. Results: The result of this present study conducted among the medical students was 72.5% found to have ‘Awareness regarding Organ Donation’, 79.31% found to have ‘Knowledge regarding Organ Donation’ and 82.5% found to have good ‘Perception about Organ Donation’.